(untitled) (Research, Society and Development, 2022)
This article of narrative review of the literature, methodologically passing through a quali-quantitative approach, aims to identify the challenges and perspectives of Rural Education in Brazil. For this purpose, the academic production, theses and dissertations, produced in the last six years (2016-2021) in Brazilian graduate programs were defined as the corpus of analysis. The survey was carried out at the Brazilian Digital Library of Theses and Dissertations (BDTD). The studies pointed out as the main challenges the lack of understanding of the principles of Rural Education on the part of professionals who work in this teaching modality, the multigrade and the insufficient financial resources destined to rural schools. As perspectives, we identified the application of didactic and methodological strategies that effectively contribute to the development of the teacher’s pedagogical work and student learning, in addition to aligning theory and daily practice in rural schools, for example, the implementation of the vegetable garden school, digital technologies/materials and the application of mathematical modeling. It is considered, according to the analyzes carried out, that the Brazilian State needs to make progress in the promotion of public policies that effectively guarantee the right of the rural population to quality education.